Rigoletto - Verdi, Giuseppe 1813-1901 (BBC Worldwide, 2000)
Verdi's drama of revenge, in its stunning new production by David McVicar, is filled with some of the composer's most celebrated music. Edward Downes conducts the Orchestra and Chorus of the Royal Opera House with a cast which includes Marcelo Alvarez, Christine Schäfer and Paolo Gavanelli. Contains nudity. (Covertext)
Interpr. u.a.: Edward Downes [Dir]. Marcelo Álvarez [Duke of Mantua]. Paolo Gavanelli [Rigoletto]. Christine Schäfer [Gilda]. The Royal Opera Chorus. The Orchestra of the Royal Opera House. David McVicar [Regie]. - Ital. mit engl., franz., dt., niederländ., und span., Untertiteln. - Aufn.: Royal Opera House, Convent Garden, 1996